Very low urinary marinobufagenin excretion reflects a high risk of disease progression in non-advanced CKD - Bolignano, Davide; Greco, Marta; Tripodi, Loredana; D’Agostino, Mario; Cianfrone, Paola; Misiti, Roberta; Pugliese, Sara; Zicarelli, Mariateresa; Musolino, Michela; Foti, Daniela Patrizia; Andreucci, Michele; Coppolino, Giuseppe (Frontiers in Physiology, 2025)
BackgroundChronic kidney disease (CKD) has now reached pandemic proportions but risk prediction towards end-stage kidney disease (ESKD) remains challenging. Kidney fibrosis is a key determinant in the transition from CKD to ESKD. In this prospective study, we investigated the prognostic significance of urinary Marinobufagenin (uMBG), a cardiotonic steroid with acknowledged pro-fibrotic activity, for stratifying the risk of CKD progression in individuals with non-advanced renal disease.MethodsAfter baseline uMBG measurements, 108 CKD patients (eGFR 40.54 ± 17 mL/min/1.73 m2) were prospectively followed up to 24 months. The study (renal) endpoint was a composite of serum creatinine doubling, eGFR decline >25% from baseline values, or ESKD requiring chronic renal replacement therapy.ResultsDuring follow-up (mean 21 months), 32.4% of patients had progressive CKD. These individuals displayed almost halved baseline uMBG excretion as compared to others (p < 0.0001). At ROC analysis uMBG showed a remarkable diagnostic capacity on CKD progression (AUC 0.898) and patients with uMBG ≤310 pmol/L (Best ROC-derived cut-off) had a significantly faster progression to the endpoint (Log-rank 57.9; p < 0.0001). Restricted cubic splines fitting logistic and Cox-regression analyses revealed that the risk association between uMBG and CKD progression was best described by a curvilinear, inverse J-shaped trend, the highest risk associated with very low uMBG levels. This trend remained unaffected by adjustment for age, baseline eGFR, and 24 h-proteinuria.ConclusionIn individuals with non-advanced CKD, very low urinary excretion of MBG reflects a more sustained risk of CKD progression over time. Validation studies are needed to generalize these findings in larger heterogeneous cohorts.